Encyclopedias and Nationalism in Denmark: A Study of the Reception of Three Encyclopedias, from Print to Digital - Simonsen, Maria (Mémoires du livre / Studies in Book Culture, 2022)
The publishing of major encyclopaedias in Denmark seldom went unnoticed. Once a publication had started, every single instalment, volume and other anniversaries were reviewed or mentioned in the nationwide newspapers and several aspects were brought up for debate: Was the publishing house able to handle such a major undertaking? What was the price of the publication and who could afford it?Attention from the press led to more than just debate of the various encyclopedias, it became an important factor in establishing the different encyclopedias as both literary works and markers of national identity. This article centres around Danish encyclopaedias and their reception in the press. The study finds that the reception was marked by one denominator in particular: the national perspective. It argues that this perspective played an important role in establishing several encyclopedias as significant national publications both of their time and legacy.